Plate Tectonics and Mineral Deposits: A View from Two Perspectives - Sangster, D. (Geoscience Canada, 1979)
Abstract Virtually all recent attempts to relate plate tectonics and mineral deposits have adopted a similar approach whereby major plate boundary regimes (e.g., spreading, subducting, transform faults, continental collision, etc.) are first described in broad terms. This is followed, or accompanied by, descriptions of the mineral deposits considered to be associated with each plate tectonic regime. A conventional approach such as this produces a list of plate-related deposits impressive in number and diversity. Closer examination of these documentation attempts, however, reveals that apart from porphyry coppers, volcanogenic massive sulphides and perhaps carbonatites, the deposit-types so considered are relatively small and inconsequential. A different perspective is attained when instead of examining mineral deposits from the plate tectonic viewpoint (the conventional approach), plate tectonics are examined relative to a list of major deposit-types. When this is done, it is evident thai many deposits cannot readily be assigned to plate tectonic regimes or processes (e.g., sandstone Cu-U-V; Precambrian banded iron-formations; Kupferscheifer Cu, etc.). Part of the problem is that many major deposit-types occur in the Precambrian for which plate tectonic processes can be documented only with difficulty, if at all. Some major Precambrian deposit-types apparently unrelated to modern-style plate tectonics would be: banded iron-formation, layered gabbroic (Sudbury) and komatiitic (e.g., Western Australia) Ni deposits, anorthosite Ti, layered mafic complexes (Cr, Pt), and conglomerate U-Au. Other deposits occur in stable regimes and, indeed, seem to require the absence of plate tectonics (e.g.. sandstone Cu-U-V; Mississippi Valley Pb-Zn; stratiform barite and phosphorite). Thus correlation of plate tectonics and mineral deposits is hampered by: a) the difficulty in "pushing" plate tectonics into the oldest rocks where many of the world's major deposits occur, and/or b) the fact that many major deposit-types occur on the (continental) plate, not at the margins, and therefore must be considered the antithesis of plate tectonic-related deposits. With all these difficulties, one can only conclude, from the perspective of a spectrum of the world's major deposit-types, that plate tectonic theory is of limited use in understanding the origin and distribution of mineral deposits.